Viral Load, CD4 Count, NLR, SGPT, and eGFR Levels as Factors Associated with Quality of Life in HIV Patients - Ahmad Jazmi Basyiruddin; Dhani Redhono Harioputro; Ratih Tri Kusuma Dewi; Eti Poncorini Pamungkasari (Gema Lingkungan Kesehatan, 2026)
Human Immunodeficiency Virus (HIV) infection remains a major global health problem and may affect the quality of life of people living with HIV. Quality of life can be assessed using the World Health Organization Quality of Life-Human Immunodeficiency Virus BREF (WHOQOL-HIV BREF) questionnaire. This study aimed to analyze the association of viral load, CD4 count, neutrophil-to-lymphocyte ratio (NLR), serum glutamic pyruvic transaminase (SGPT), and estimated glomerular filtration rate (eGFR) with quality of life among HIV patients. This observational analytic study used a cross-sectional design and was conducted at the Voluntary Counseling and Testing Clinic of Dr. Moewardi Hospital, Surakarta, Central Java, Indonesia. A total of 100 HIV patients undergoing antiretroviral therapy were included based on predefined inclusion and exclusion criteria. The independent variables were viral load, CD4 count, NLR, SGPT, and eGFR, while the dependent variable was quality of life assessed using the WHOQOL-HIV BREF questionnaire. Clinical and laboratory data were obtained from medical records. Data were analyzed using univariate analysis, Spearman correlation test, and ordinal logistic regression with SPSS version 29.0. Higher viral load, lower CD4 count, and elevated NLR were significantly associated with poorer quality of life. In contrast, SGPT and eGFR were not significantly associated with quality of life. In the multivariate analysis, CD4 count showed the strongest association with quality-of-life category. These findings suggest that viral load, CD4 count, and NLR are associated with quality of life among HIV patients. The integration of virological, immunological, and inflammatory markers may complement clinical assessment of quality of life in people living with HIV, particularly in the Indonesian clinical setting. Further longitudinal studies are needed to clarify their predictive value.